Linguo-semiotics of national identity in the field of digital public diplomacy - Kozlovskaya, Lyudmila A. (Journal of the Belarusian State University. Philology, 2023)
The object of this study includes basic information, reference and news materials of several foreign embassies’ (diplomatic representative offices’) official websites in Belarus. The purpose of the article is a comparative study of state languages use by these platforms as a linguo-semiotic means of national identity, as well as news materials of these sites in the aspect of determining the degree of their national marking. The research data could be used in studies of languages’ social (functional) typology, as well as in practice of development and effective maintenance of similar profile sites.
Keywords: national identity; ethnic identity; digital diplomacy; language situation; linguo-semiotics of national identity